(3cJGH fGFH Hf bQI aj GdGYOGO GdeJMGHIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI cd YOO SWM VdYGg YOOGf ChdGf adjS HYOI YOI BNQ ZjQg s
(3BNQgG (B:s
(3hEf Pdc jchf eKd aUd eG Hjf GdYOOjf GfaSgeG hCfg EPG CNP cd LRA dcd hGMO efgeG hLeY Pdc cdg eYkG cGfJ LedI Pdc eKd s
(3Vef eLehY , JQJjHgG (B: 6s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs